A PERFORMANCE MEASUREMENT IN THE FRAMEWORK OF THE BALANCED SCORECARD: ITS IMPLEMENTATION AT THE PUBLIC SECTOR - Biswan, Ali Tafriji; Sholikhah, Mar'atus; Sandi, Hendrik Heri (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study aimed to reveal the essence of the uniqueness of the balanced scorecard practice in the public sector based on its dynamics and characteristics. This qualitative research utilized a case study model combining literacy, data processing, in-depth interviews, and the researchers’ involvement. The results of the study indicate that the balanced scorecard can be adapted to an organization's vision and mission. Meanwhile, the customer perspective can be further divided into several perspectives, such as service partners and the stakeholder perspective, which became the ultimate goal of services. However, the financial aspect remained important and relevant for the object of the study even though it was not developed into a financial perspective independently. Instead, this aspect is included as a strategic objective from the perspective of learning and growth. In addition, the sharpening of the Key Performance Indicators (KPI) is also carried out after the results of the KPI achievement are measured and evaluated. Keywords: Performance Measurement, Balanced Scorecard, Key Performance Indicators, Public Sector.